Trend or disease? - gluten-free diet - Zimna, Aleksandra Iwona; Chojęta, Dariusz; Wróblewski, Hubert; Zygmunt, Ewelina; Maziarz, Barbara (Journal of Education, Health and Sport, 2020)
Introduction and purpose of work: Over the past few years, the topic of gluten-free diets has become very popular. In the past, it was understood only in the context of a specific medical indication, implemented in the event of a disease, e.g. celiac disease, as part of the patient’s treatment. Today, the concept has changed a bit. The abatement of the concept of a gluten-free diet is attributed to social media, which, in a way, suggests recipients to use it on a daily basis, clearly emphasizing the harmful effects of gluten on the human body. better mood". The aim of the study is to analyze the awareness of the society on the use of a gluten-free diet. Material and method: The results of the study were obtained on the basis of an online survey. Results: 213 respondents took part in the survey, 36.2% of the respondents were women and 63.8% men, 88.7% of the surveyed respondents correctly answered the question what gluten is, but 65.7% are associated with the presence of gluten in products food industry with the development of this industry, 42.3% of respondents believe that consumption of gluten should be avoided. Only 8.9% of people on a gluten-free diet heard from a doctor for the first time, over 36% from the media. As many as 78.4% of respondents are not aware of about the need to balance this diet, but still uses it. Conclusions: The study shows that the society is not fully educated on the use of a gluten-free diet. It can be concluded that the approval of the society is not based on the merits, but rather an expression of a trend. The dissemination of this concept is due to the media.